Electroluminescence from solution-processed pinhole-free nanometer-thickness layers of conjugated polymers - Newby, Carol; Vaynzof, Yana (Nano letters, 2018)
We report the formation of robust, reproducible, pinhole-free, thin layers of fluorinated polyfluorene conjugated copolymers on a range of polymeric underlayers via a simple solution processing method. This is driven by the different characters of the fluorinated and nonfluorinated sections of these polymers. Photothermal deflection spectroscopy is used to determine that these layers are 1-2 nm thick, corresponding to a molecularly thin layer. Evidence that these layers are continuous and pinhole-free is provided by electroluminescence data from polymer LED devices that incorporate these layers within the stacked LED structure. These reveal, remarkably, light emission solely from these molecularly thin layers.
Gesehen am 21.02.2020